Prove that

C(n+1,r) = C(n,r)+ C(n,r-1)

~~~~~
I know the defintion of a combination is... C= n!/(n-r)!r! but i still cant get left side to equal right side. help.

defn.

C(n,r) = n!/((n-r)!r!)

LS = (n+1)!/(r!(n+1-r)!)

RS = n!/((n-r)!r!) + n!/((r-1)!(n-r-1)!)

now recall that something like 5x4! = 5!
then in the same way if I have n! and multiply it by n+1 I would get (n+1)!

so back to
RS = n!/((n-r)!r!) + n!/((r-1)!(n-r-1)!)
I will multiply the top and bottom of the first fraction by
(n-r+1)
and I will multiply the top and bottom of the second fraction by r
simplifying this (without typing that mess) I get
RS = n!(n-r+1)/((n-r=1)!r!) + (n!r/(n-r+1)!r!)
notice we now have a common denominator, so we add up the top.
But I see a common factor of n! in the top , so
RS = n!(n-r+1 - r)/((n-r+1)!r!)
= n!(n+1)/((n-r+1)!r!)
= (n+1)!/((n-r+1)!r!)
= LS

http://answers.yahoo.com/question/index?qid=20071130201604AAy0UBp

That should guide you. IT is not exactly the same, but you can follow it.

To prove that C(n+1,r) = C(n,r) + C(n,r-1), let's first expand both sides of the equation using the definition of combination.

Left side: C(n+1,r) = (n+1)! / [(n+1-r)! * r!]

Right side: C(n,r) + C(n,r-1) = n! / [(n-r)! * r!] + n! / [(n-r+1)! * (r-1)!]

Let's simplify the right side to see if it matches the left side:

Right side: [n! * (n-r+1)] / [(n-r)! * r!] + [n! * r] / [(n-r+1)! * (r-1)!]

Now, let's find the common denominator of the two fractions on the right side:

Right side: [n! * (n-r+1) * (n-r)] / [(n-r)! * r! * (n-r+1)] + [n! * r * r] / [(n-r+1)! * (r-1)! * r]

Now, we can combine the two fractions:

Right side: [n! * (n-r+1) * (n-r) + n! * r * r] / [(n-r)! * r! * (n-r+1)]

Next, let's simplify the numerator:

Right side: [n! * (n-r+1) * (n-r) + n! * r * r] / [(n-r)! * r! * (n-r+1)]
= [n! * (n-r+1) * (n-r) + n! * r * r] / [n! * (n-r)! * r! * (n-r+1)]

Now, we can cancel out the common factors:

Right side: [(n-r+1) * (n-r) + r * r] / [(n-r+1)! * r!]
= [(n² - 2nr + r²) + r²] / [(n-r+1)! * r!]

Simplifying further:

Right side: [n² - 2nr + 2r²] / [(n-r+1)! * r!]

Now, let's compare this with the left side:

Left side: (n+1)! / [(n+1-r)! * r!]

We can rewrite (n+1)! as (n+1) * n!

Left side: [(n+1) * n!] / [(n+1-r)! * r!]

Now, notice that (n+1-r)! can be written as (n+1-r) * (n-r)!

Left side: [(n+1) * n!] / [(n+1-r) * (n-r)! * r!]

Now, observe that the numerator of the right side matches the numerator of the left side:

Right side numerator: n² - 2nr + 2r²
Left side numerator: (n+1) * n!

Therefore, we can conclude that:

C(n+1,r) = C(n,r) + C(n,r-1)